2017
DOI: 10.1021/acs.est.7b00985
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Toxicity of Complex Mixtures of Polycyclic Aromatic Hydrocarbons: Evaluating Dose-Additivity in a Transgenic Mouse Model

Abstract: This study evaluates the risk assessment approach currently employed for polycyclic aromatic hydrocarbon (PAH)-contaminated media, wherein carcinogenic hazards are evaluated using a dose-addition model that employs potency equivalency factors (PEFs) for targeted carcinogenic PAHs. Here, MutaMouse mice were subchronically exposed to PAH mixtures (p.o.), and mutagenic potency (MP) values were determined for five tissues. Predicted dose-additive mixture MPs were generated by summing the products of the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Polycyclic aromatic hydrocarbons (PAHs) generally refer to hydrocarbons that have two or more benzene rings [1,2]. PAHs, commonly known as carcinogens, mutagens, teratogens, and bioaccumulators, can cause great damage in humans and the environment [3,4,5,6,7,8]. They are also a part of the atmospheric particulate pollutant PM 2.5 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) generally refer to hydrocarbons that have two or more benzene rings [1,2]. PAHs, commonly known as carcinogens, mutagens, teratogens, and bioaccumulators, can cause great damage in humans and the environment [3,4,5,6,7,8]. They are also a part of the atmospheric particulate pollutant PM 2.5 [9].…”
Section: Introductionmentioning
confidence: 99%
“…The CCME [ 11 ] noted the PEF approach tended to underestimate the potency of coal tar and creosote mixtures typically found at contaminated sites. They therefore adopted a three-fold safety factor when using a relative potency approach to calculate the toxicity of creosote or coal tar mixtures; however, few other jurisdictions have applied a similar safety factor for PAH mixtures, and at least one recent study [ 18 ] found only modest deviations from additivity of priority PAHs when assessing the toxicity of two coal tars and one coal-tar-based pavement sealant.…”
Section: Discussionmentioning
confidence: 99%
“…Potency only provided for comparative purposes. 6 Long et al, 2017 [ 18 ]. Table S2 : A literature review was conducted to identify the lowest and highest published PEFs for each compound.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, combined genotoxic effects have been demonstrated in vitro for the alkylating agents methyl methanesulfonate and ethyl methanesulfonate (Kojima et al 1992 ) and also for a polycyclic aromatic hydrocarbon (benzo [a] pyrene) and a heterocyclic amine (2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine) (Jamin et al 2013 ). Moreover, in vitro and in vivo mutagenicity studies on mixtures of polycyclic aromatic hydrocarbons supported the assumption of dose additivity (Lemieux et al 2015 ; Long et al 2017 ).…”
Section: Challenges Arising From a Quantitative Interpretation Of Gen...mentioning
confidence: 95%